Bali Government’s Strategic Plan to Introduce Kusamba Salt Worldwide - Ida Bagus Komang Surya Werdiyasa (Bali Tourism Journal, 2022)
In Bali, Kusamba village in Klungkung regency has been known as a Salt producer village. Despite its final premium product, it has not been marketed with attractive packaging to elevate its value. The salt has low iodine content, making it unattractive compared to most table salt products. Realising the potential, the Governor of Bali, Wayan Koster, suggested to improve its marketing strategy thus the salt farmer could yield a huge benefit once the product value is well-optimized. The idea was fully supported by the Regent of Klungkung, Nyoman Suwirta. Further, Suwirta pointed out the vision to bring the local product domestically and globally since the salt-making process in Kusamba has a sentimental taste historical value for the society. The salt industry is a strategic sector that needs to be developed, considering that Indonesia is still dependent on imported products despite having vast marine potential. Assistances from Government and private sector becomes a possible solution, to elevate the commodities standard thus the high-quality local salt might be accepted by Global communities.